Controlled formation of bubbles in a planar co-flow configuration. (March 2017) - Ruiz-Rus, J.; Bolaños-Jiménez, R.; Gutiérrez-Montes, C.; Sevilla, A.; Martínez-Bazán, C.
Highlights: A novel technique to force the bubble pinch-off in a water-air-water planar co-flow configuration is presented. The forcing process consists of a perturbation of the water velocity. Smaller bubbles at higher frequencies than in the natural process are produced. The forcing method is characterized experimentally. A one-dimensional model that describes the experimental and numerical air-water interface is proposed. Abstract: We present a new method that allows to control the bubble size and formation frequency in a planar air-water co-flow configuration by modulating the water velocity at the nozzle exit. The forcing process has been experimentally characterized determining the amplitude of the water velocity fluctuations from measurements of the pressure variations in the water stream. The effect of the forcing on the bubbling process has been described by analyzing the pressure signals in the air stream in combination with visualizations performed with a high-speed camera. We show that, when the forcing amplitude is sufficiently large, the bubbles can be generated at a rate different from the natural bubbling frequency, fn, which depends on the water-to-air velocity ratio, Λ = u n / u a, and the Weber number, W e = ρ w u n 2 H o / σ, where Ho is the half-thickness of the air stream at the exit slit, ρw the water density and σ the surface tension coefficient. Consequently, when the forcing is effective, monodisperse bubbles, of sizes smaller than those generated without stimulation, are produced at the prescribed frequency, ff > fn . The effect of the forcing process on the bubble size is also characterized by measuring the resulting intact length, li, i.e. the length of the air stem that remains attached to the injector when a bubble is released. In addition, the physics behind the forcing procedure is explained as a purely kinematic mechanism that is added to the effect of the pressure evolution inside the air stream that would take place in the unforced case. Finally, the downstream position of the maximum perturbation amplitude has been determined by a one-dimensional model, exhibiting a good agreement with both experiments and numerical simulations performed with OpenFOAM.